Preliminary design of a hybrid wave energy converter integrated in a breakwater - Ashank Sinha (2019)
Sea ports are highly exposed to ocean waves, being often necessary to protect them with breakwaters and other sheltering solutions. Also, ports are infrastructures with substantial energy demands and major sources of air pollution and other environmental impacts. By using renewable energy, in particular electricity harvested from ocean waves, ports would be able to convert some of the disadvantages associated with the harsh ocean environment into a potential solution for the problem of large energy demands and pollution. In fact, many ports worldwide already started the transition to cleaner energy sources in order to decarbonize their activities and meet their future renewable energy targets. The high potential of port breakwaters for the integration of Wave Energy Converters (WECs) triggered the European SE@PORTS project (OCEANERA-NET), which aims to assess the suitability and viability of existing energy conversion technologies to be integrated into such infrastructures. The present paper introduces the preliminary design of a hybrid WEC solution that combines the concepts of Oscilating Water Column (OWC) and OvertoppingWave Energy Converter (OWEC).Thishybrid WEC was developed taking into consideration the characteristics of the north breakwater of the Port of Leixões, Portugal, and the proposed plan for its extension. In order to simulate the physical phenomenon behind the OWC, a waveto-wire model was developed in MATLAB SIMULINK. The performance of the OWEC was estimated resorting to the code WOPSIM (Wave Overtopping Simulation). Both tools were used to assist in the optimization of the hybrid WEC design. Some of the preliminary results are presented in this paper.